2018
DOI: 10.1007/s00418-018-1642-4
|View full text |Cite
|
Sign up to set email alerts
|

1700108J01Rik and 1700101O22Rik are mouse testis-specific long non-coding RNAs

Abstract: Long non-coding RNAs (lncRNAs; > 200 nucleotides in length) have attracted attention as fine-tuners of gene expression. However, little is known about the cell- and stage-specific expression pattern and function of lncRNAs in spermatogenesis. The purpose of this study was to identify mouse testis-associated lncRNAs using a combination of computational and experimental approaches. We first used the FANTOM5 database to survey lncRNA expression in the mouse testis and performed reverse transcription quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Furthermore, correlation analysis between mRNAs and lncRNAs showed high correlation coefficients and suggested coordinated changes in their expression during the biogenesis and function of male spermatogenesis. A similar investigation reported the expression of antisense lncRNA 1700108J01Rik and long intergenic noncoding RNA 1700101O22Rik [53] in meiotic prophase and round spermatid stages in testicular germ cells. Similarly, Dai et al reported higher expression of lncRNA-testicular cell adhesion molecule 1 (lncRNA-Tcam1) in round spermatids than in somatic cells or germ cells in mice, with lncRNA-Tcam1 being localized in 45% of the cells found in testis [55].…”
Section: Eduau/nredmentioning
confidence: 65%
See 4 more Smart Citations
“…Furthermore, correlation analysis between mRNAs and lncRNAs showed high correlation coefficients and suggested coordinated changes in their expression during the biogenesis and function of male spermatogenesis. A similar investigation reported the expression of antisense lncRNA 1700108J01Rik and long intergenic noncoding RNA 1700101O22Rik [53] in meiotic prophase and round spermatid stages in testicular germ cells. Similarly, Dai et al reported higher expression of lncRNA-testicular cell adhesion molecule 1 (lncRNA-Tcam1) in round spermatids than in somatic cells or germ cells in mice, with lncRNA-Tcam1 being localized in 45% of the cells found in testis [55].…”
Section: Eduau/nredmentioning
confidence: 65%
“…The ChIPBase, NPInter, miRcode, DIANA-LncBase, StarBasev2.0, lncRNA2Target, and lncRNADisease are examples of interaction databases. The specific databases include lnCeDB, NRED, Linc2go, and lncRNASNP [49][50][51][52][53][54][55][56][57][58][59].…”
Section: Databases Of Lncrnasmentioning
confidence: 99%
See 3 more Smart Citations